THE SOLUBILITY OF PT IN LIQUID FE-SULFIDES - Pruseth K.L.; Palme H. (My University, 2004)
The partitioning of Pt between liquid sulfides with approximately stoichiometric FeS and Pt–Fe alloys was experimentally studied. Experiments were conducted in corundum crucibles enclosed in evacuated quartz vials heated to 1100, 1200 and 1300 °C. Starting materials were Pt metal and sulfides of Fe70S30 composition. Run products were coarse Pt–Fe alloys and quenched sulfide melts crystallized to FeS and dendrites of Pt–Fe alloys. All phases were analyzed with the electron microprobe (EMP) and the composition of average sulfide melt was calculated. The Pt contents of sulfide melts increase from 0.01 to nearly 10 at.% with S contents increasing from 45 to 50 at.%. Metal/liquid sulfide atom ratios of Pt range from 3 to 1400. After recalculating the data to unit Pt activity in metal, rather constant Pt contents in sulfides were obtained for S-rich systems with fS2 above 10−4 atm. On average, 13.1±6 at.% Pt (or 53±22 wt.% Pt) would be dissolved in liquid sulfides in equilibrium with Pt at unit Pt activity. By using the Pt solubilities in sulfides obtained here and those in silicates measured by Borisov and Palme [Geochim. Cosmochim. Acta 61 (1997) 4349] and by assuming the fO2 to be defined by the QFM buffer, Pt liquid sulfide/silicate partition coefficients, DPtSul/Sil, were calculated. These partition coefficients are several orders of magnitude higher than those experimentally determined. The most likely reason is the formation of Pt-rich nuggets in partition experiments.